MERKEZİ FONKSİYONLARI AÇISINDAN AĞIN-ARAPGİR VE KEMALİYE İLÇELERİ - KARAKAŞ, ERDAL (Fırat Üniveristesi, 1996)
Ağın, Arapkir and Kemaliye subjected to our study are in the part of Anatolia. Ağın is in Elazığ, Arapkir is in Malatya and Kemaliye is in Erzincan. The population of these towns fell down in the different time of the history according to the reasons of the wars and their economies. As a matter of fact the population of Arapkir was 20,000, the population of Kemaliye was 19.000 and the population of Ağın was 800 in 1 891 while the population of Arapkir was 6782, the population of Kemaliye was 5428 and the population of Ağm was 1000 in 1927 and sometimes their populations fell down less than the one above. There are some differences in the towns between the past and present activities. The commercial and the Industrial activities developed depending on the caravan trade in the 18 th century made no progress according to the changes of the transportations while the commercial and Industrial activities became important in this period of the time in Arapkir and Kemaliye. In the previous years, the administration activities got a great importance in these towns although it was late. In 1990, 69.1 percent of the population in Ağm. 63.2 percent in Arapkir and 64.4 percent in Kemaliye have been taken in to the Administration service. According to these results, the service in Ağm is related to the admimstriation and agriculture activities, the one in Arapkir is related to the administration and commercial activities and the one in Kemaliye is related to the adrninistration and industrial activities.
Ağın-Arapkir and Kemaliye in point of central functions
Keywords: Coğrafya; Geography